Effects of P2O5/TiO2 ratio on the sintering behavior and microwave dielectric properties of TiP2O7. Issue 3 (April 2015) - Wang, Y.N.; Bian, J.J.
Abstract: TiP2 O7 ceramics with various P2 O5 /TiO2 ratios were prepared by the traditional solid-state process. Constituent phases and microstructure were investigated by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Microwave dielectric properties were studied with a network analyzer in the frequency range 10–13 GHz. Although phase pure TiP2 O7 could be obtained for the stoichiometric and P-excess compositions after calcining at 900 °C, (TiO)2 P2 O7 secondary phase occurred for all compositions after sintering at 1250 °C/2 h. Phase pure TiP2 O7 ceramic could not be obtained due to the evaporation of P2 O5 at sintering temperature, although excessive P2 O5 and muffling with sacrificial powder were adopted. P-deficiency increased the amount of (TiO)2 P2 O7 impurity phase. The stoichiometric and P-excess compositions demonstrated poorer densification and hence lower dielectric permittivities but higher Qf values than those of P-deficient compositions. Good optimized microwave dielectric properties with ε r 11, Qf 77, 000 GHz, and τ f 14 ppm/°C could be obtained for the stoichiometric and P-excess compositions.